Impact of the use of technological tools aquaculture - Guélac Gómez, Jhordani; Sánchez Calle, Jeison Elí; Valles-Coral, Miguel Angel (Enfoque UTE, 2023)
Peruvian aquaculture is booming, so it deserves to be technified from a sustainable and competitive perspective. The objective of the review was to identify the current panorama of Peruvian aquaculture and the factors that limit its development, as well as to analyze the benefits of the use of technological tools in aquaculture. To this end, a review methodology was applied based on three phases: i) development of the research question; ii) document search; and ii) review and selection of studies. The search engine used was Google Scholar, Scopus, ScienceDirect, Web of Science (WOS), Scielo and Redalyc databases. The review showed that aquaculture in Peru is developed in few regions and with few species. According to PNIPA, the factors limiting its development are related to noncompliance with current sanitary regulations, vessels that are not registered in public registries, and the absence of accreditation controls for artisanal fishermen. Technification of the feeding process reduces operating costs. Sensors make it possible to visualize the variation of parameters in real time, reducing the fish mortality rate. Automatic counting and classification reduces fish stress and avoids economic damage to production. The conclusion is that, in order to achieve aquaculture technification, the government and producers must work together, implementing policies and strategies that guarantee greater profitability and sustainability over time.